Analysis of Flood Discharge in the Balangan Sub-Watershed Using HEC-HMS - Erisa, Erisa; Helda, Noordiah (Universitas Negeri Semarang, 2025)
Flooding poses significant challenges, especially in areas with rapid urban development, such as Balangan Regency, South Kalimantan. This study analyzes the hydrological conditions contributing to floods in the Balangan River watershed using the HEC-HMS (Hydrologic Modeling System). The research employs secondary data, including rainfall data from GSMaP (Global Satellite Mapping of Precipitation), watershed delineation from DEMNAS, and soil type data from Google Earth Engine. Precipitation data spanning 20 years (2003–2022) were analyzed using the Thiessen Polygon Method and statistical tests such as chi-square and Smirnov-Kolmogorov for distribution fitting. Hydrological modeling was conducted using the SCS Curve Number method integrated into HEC-HMS to estimate flood discharges for various return periods. The results indicate peak discharges of 2,916.8 m³/s, 4,309.7 m³/s, 5,590.8 m³/s, 7,288.5 m³/s, 9,625.8 m³/s, and 11,943.4 m³/s for return periods of 2, 5, 10, 20, 50, and 100 years, respectively. These findings highlight the critical impact of land cover, soil characteristics, and rainfall patterns on flood risks. The study underscores the importance of incorporating hydrological modeling tools like HEC-HMS for effective flood risk management and planning in the region.